Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Kooperatif Tipe Snowball Throwing di Kelas V Sekolah Dasar - Mardalena, Irma; Ahmad, Syafri (Universitas Negeri Padang, 2024)
This study intends to show how the Snowball Throwing cooperative model has improved integrated theme learning outcomes for class V SDN 05 Padang Pasir. Classroom action research (CAR) is this kind of study. Which is a form of research that combines both qualitative and quantitative techniques. 26 persons, including instructors and fifth graders, were the study's subject at SD Negeri 05 Padang Pasir Padang. (1) The lesson plan increased from an average proportion of the initial cycle of 86.11% with a very good predicate (B) to an average percentage of the second cycle of 91.66% very good (SB). (2) From cycle I which has an average of 86.11% with a good predicate (B), cycle II's very strong predicate (SB) of 94.44% for cycle II results in the assertion that the use of learning through aspects felt by the teacher is increasing. While the aspects seen in students increased from cycle I on average 87.50% good (B), to cycle II, namely 91.66% very good (SB). The Snowball Throwing cooperation model, it may be argued, can enhance fifth grade kids' learning processes at SDN 05 Padang Pasir in integrated thematic learning in Padang City.